English Extracurricular Activities in Developing Language Intelligence at SMP Plus Al Munawaroh Jember - Aliyah, Sofiatil; Machfudi, Moch. Imam; Suratinah, Suratinah (Journal of English for Academic and Specific Purposes (JEASP), 2023)
Extracurricular activities are educational activities that take place outside of traditional classroom settings. These activities take place inside and/or outside of the school environment in order to broaden knowledge, improve skills, and internalize religious values or laws, as well as local, national, and global social norms. This is a qualitative study, which stresses the meaning and process of an activity rather than the outcome of an activity. By referring to the data taken from teacher and students’ involvement in the extracuricular activities and based on the results of observations and interviews, this study reveals  that the majority of students are engaged in the extracuricular activities and benefit greatly from them. Aside from that, the activity facilitated teachers in carrying out coaching, direction, care, and supervision in order to achieve the desired results. Students' language intelligence in learning English at SMP Plus Al Munawaroh Tempurejo Jember was formed by an acivity to communicate with others, both with their peers and with their teachers, using English even though it was often mixed up with their native language. Students were also engaged to perform their learning outcomes in many stages of learning.